From Autocracy to Empowerment: Teams with Shared Leadership Perceive their Coaches to be Better Leaders. Issue 1 (2nd January 2020) - Fransen, Katrien; Mertens, Niels; Cotterill, Stewart T.; Vande Broek, Gert; Boen, Filip
Abstract : Sports coaches often fear that empowering the players in their team would undermine their own leadership status. To investigate the legitimacy of this perception, we mapped the leadership structure within 64 sports teams (N = 840). The results highlight that the perceived leadership quality of the coaches is positively related to the density of their team's leadership networks (i.e., the average leadership qualities of all players). This finding held for task, motivational, social, and external leadership. The best coaches are thus the ones who adopt a shared leadership approach and who strengthen the leadership quality of their players. Lay Summary Sports coaches often feel that empowering the players in their teams undermines their own leadership status. This study investigates the legitimacy of this perception within 64 sports teams. Our findings provide evidence for the opposite view; by creating and developing leaders in their teams, coaches are perceived as better leaders themselves.